Roles of the ventral hippocampus and medial prefrontal cortex in spatial reversal learning and attentional set-shifting - Cernotova, Daniela; Stuchlik, Ales; Svoboda, Jan (Neurobiology of learning and memory, 2021)
Neural components enabling flexible cognition and behavior are well-established, and depend mostly on proper intercommunication within the prefrontal cortex (PFC) and striatum. However, dense projections from the ventral hippocampus (vHPC) alter the functioning of the medial PFC (mPFC). Dysfunctional hippocampo-prefrontal connectivity negatively affects the integrity of flexible cognition, especially in patients with schizophrenia. In this study, we aimed to test the role of the vHPC and mPFC in a place avoidance task on a rotating arena using two spatial flexibility task variants - reversal learning and set-shifting. To achieve this, we inactivated each of these structures in adult male Long-Evans rats by performing bilateral local muscimol (a GABAA receptor agonist) injections. A significantly disrupted performance was observed in reversal learning in the vHPC-inactivated, but not in the mPFC-inactivated rats. These results confirm the notion that the vHPC participates in some forms of behavioral flexibility, especially when spatial cues are needed. It seems, rather unexpectedly, that the mPFC is not taxed in these flexibility tasks on a rotating arena.
Keywords: agonisté receptorů GABA-A; Ventral hippocampus; Prefrontal Cortex; prefrontální mozková kůra; Attention; prostorové vidění; Rotating arena; krysa rodu Rattus; Hippocampus; Prefrontal cortex; Behavioral flexibility; reverzní učení; zvířata; Avoidance Learning; Spatial Processing; hipokampus; učení vyhýbat se; Reversal Learning; Male; GABA-A Receptor Agonists; Carousel; Rats; muscimol; Animals; Muscimol; mužské pohlaví; pozornost